An Effect of Screw Extrusion Parameters On a Pottery Model Forming by A Clay Printing Machine - Pitayachaval, Paphakorn; Baothong, Thanakharn (International Journal of Integrated Engineering, 2022)
This paper presents a study of the screw extrusion parameters that effect on the appearance of clay filament for a clay printing machine. Traditionally, pottery models are formed by using paster mold or hand throwing, which require experience and proficient workers to form the complex pottery models. Therefore, the clay printing machine has been developed to improve pottery manually fabrication to automatic construction. This machine has been modified based on the additive manufacturing (AM). To assess a capability material deposition of the clay printing machine, nozzle diameter, screw extruder velocity, and screw pitch were investigated as the printing parameters to evaluate a quality of clay filament. Analysis of variance (ANOVA) is used to analyze main effect parameters. The experimental results shown that the 6 mm nozzle diameter, 19 mm/s screw extruder velocity and 24 mm screw pitch were printing parameters for providing an appropriate appearance of clay filament. A mathematical model was formulated to propose the relationship between response and main effects with their interactions.